The new color mixing companion : explore and create fresh and vibrant color palettes with paint, collage, and mixed media - Lewis, Josie (Quarry Books, an imprint of The Quarto Group, 2019)
"This comprehensive guide starts with a crash course in essential terminology and visual vocabulary, then shows you how to go beyond the wheel and basic theory with hands-on projects that illustrate and illuminate a variety of color elements and techniques. The materials used--including watercolor and acrylic paints, and found or purchased collage papers--are accessible, inexpensive, and readily available. Plus, this art guide includes easy-to-use templates featured in many of the projects; their modern geometric layouts yield stunning color arrangements."--Amazon